HUBUNGAN TINGKAT PENDIDIKAN DAN USIA DENGAN KEJADIAN HIPERTENSI - Satiyem, Satiyem; Murtiningsih, Dewi; Pradessty, Adzhana Dhiva (Jurnal Kebidanan, 2024)
Background: Hypertension is a non-communicable disease which is a health problem that can cause the highest number of deaths in the world. Lack of education and knowledge means a person will be more susceptible to hypertension due to a lack of knowledge about healthy food. where individuals with a better level of education will make efforts to maintain health more appropriately. As age increases, the body's immune system decreases and unhealthy eating patterns will result in hypertension. Objective: To determine the relationship between education and age with the incidence of hypertension. Research Methods: This research is a quantitative cross-sectional research. The research location is Kedungwinong Nguter Village, Sukoharjo. The sample in this study was 45 people. The sampling technique uses a nonprobability sampling method with random sampling technique. Univariate data analysis and bivariate person correlation with an error rate of 5% (α = 0.05). Results: There was a significant positive relationship between education level and the incidence of hypertension (p 0.000; r 0.806) and age and the incidence of hypertension (p 0.000; r 0.740). Among the two variables that are most at risk is education. Conclusion: There is a significant relationship between education level and age and the incidence of hypertension